MOOC courses development: guidelines for GLAM MOOC / Mazwani Ayu Mazlan, Zarina Zainol and Nurzalina Harun - Mazlan, Mazwani Ayu; Zainol, Zarina; Harun, Nurzalina (Universiti Teknologi MARA, Kedah, 2024)
Massive Open Online Courses (MOOCs) have dramatically changed the higher education landscape by providing flexible and accessible learning options to learners globally. Creating efficient MOOCs that meet learners' unique demands becomes crucial in the field of information science, consisting of Galleries, Libraries, Archives, and Museum (GLAM) management, where ongoing upgrades and developments are essential. The development methods used by information science lecturers to produce MOOCs for higher education are thoroughly discussed in this article. This article concentrates on strategies and methods utilized by the School of Information Science MOOC coordinator in designing and delivering MOOCs. It examines the critical factors, including instructional design principles, technology integration, and learner engagement techniques. Furthermore, this article highlights the obstacles lecturers encounter during the development process and creative solutions created to overcome them. In addition to preparing those interested in or supervising the development of MOOC courses, the methods will provide insights for enhancing MOOC design, enhancing learner engagement, and addressing the specific requirements of information science education. This article hopes to contribute to the development and supervision of online learning content and to promote accessible and efficient education in the field of information science.